Comparative study and new metric for video shot boundary detection - Jayaratchagan Nagamani (2008)
With the rapidly increasing video data, segmentation of video streams into shots has become evermore important in the area of content-based indexing, characterizing, and retrieving of video. A shot is a temporal sequence of frames generated and recorded continuously by a single camera act. To form a video sequence, shots are joined together during video sorting or post editing.